2017
DOI: 10.1101/gad.302695.117
|View full text |Cite
|
Sign up to set email alerts
|

Settling the m6A debate: methylation of mature mRNA is not dynamic but accelerates turnover

Abstract: Post-transcriptional modification of RNA nucleosides has been implicated as a pivotal regulator of mRNA biology. In this issue of Genes & Development, Ke and colleagues (pp. 990-1006) provide insights into the temporal and spatial distribution of N 6 -methyladenosine (m 6 A) in RNA transcripts by analyzing different subcellular fractions. Using a recently developed biochemical approach for detecting m 6 A, the researchers show that m 6 A methylations are enriched in exons and are added to transcripts prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 9 publications
(10 reference statements)
0
29
1
Order By: Relevance
“…Approaching sub‐cellular organelle resolution (beyond separating cytoplasm from nuclei and mitochondria) has not yet been achieved in RNA modification research. Addressing RNA content, structure and modification status in individual BioMCs using improved biochemical and structural methodology might be an interesting path forward, especially for an emerging field called “epitranscriptomics” that is presently trying to reconcile the low stoichiometry of detectable RNA modifications, specifically in mRNAs, with the reported adverse effects of RNA modification system mutations on cellular and organismal physiology …”
Section: Discussionmentioning
confidence: 99%
“…Approaching sub‐cellular organelle resolution (beyond separating cytoplasm from nuclei and mitochondria) has not yet been achieved in RNA modification research. Addressing RNA content, structure and modification status in individual BioMCs using improved biochemical and structural methodology might be an interesting path forward, especially for an emerging field called “epitranscriptomics” that is presently trying to reconcile the low stoichiometry of detectable RNA modifications, specifically in mRNAs, with the reported adverse effects of RNA modification system mutations on cellular and organismal physiology …”
Section: Discussionmentioning
confidence: 99%
“…Writing m 6 A mRNA-modifying enzymes are often referred to as writers, by analogy with signal transduction systems in which writers catalyze the formation of a regulatory posttranslational modification, readers act as effectors by binding to the modified amino acid, and erasers remove the modification to reset signaling (Lim and Pawson, 2010). We adopt this nomenclature here but note that its appropriateness is intensely debated, because it is difficult to obtain direct proof that the same mRNA molecules undergo reversible cycles of methylation and demethylation Mauer et al, 2017Mauer et al, , 2019Meyer and Jaffrey, 2017;Rosa-Mercado et al, 2017;Darnell et al, 2018;Wei et al, 2018a;Shi et al, 2019). Despite the simple biochemistry of the m 6 A writer reaction, nucleophilic substitution resulting in transfer of the methyl group from S-adenosylmethionine (SAM) to the N 6 -amine of adenosine, the major eukaryotic mRNA adenosine methyltransferase turns out to be extraordinarily complicated.…”
Section: Occurrence Of M 6 a In Plant Transcriptomesmentioning
confidence: 99%
“…Still, it is also possible that depletion of these RNA demethylases results in an indirect effect in the HIV-1 replication cycle. In this regard and considering that the reversibility of adenosine methylation was recently challenged ( Darnell et al, 2017 ; Ke et al, 2017 ; Rosa-Mercado et al, 2017 ), it is very important to determine whether HIV-1 transcripts are indeed hypermethylated in ALKBH5 and FTO knockdown cells.…”
Section: Discussionmentioning
confidence: 99%
“…Despite FTO has been shown to demethylate the body of certain mRNAs ( Zhao et al, 2014 ), it was recently reported that the N 6 ,2′- O -dimethyladenosine (m 6 Am) modification adjacent to the 7-methylguanosine cap structure rather than m 6 A is the main substrate of this demethylase ( Mauer et al, 2016 ). Moreover, although ALKBH5 is now considered as the major m 6 A eraser of mRNA, the reversibility of the methylation process in cells has been recently challenged ( Darnell et al, 2017 ; Ke et al, 2017 ; Rosa-Mercado et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%